Absolute quantification revealed that glutamate increased the abundance of the rhizosphere bacterial community in Camellia oil tree under drought stress - Lu, Kaizheng; Zhou, Junqin; Yuan, Jun; Qiu, Jiaqi; Tan, Xiaofeng (Frontiers in Microbiology, 2025)
IntroductionSeasonal drought associated with the subtropical monsoon climate significantly impairs the growth and development of Camellia oil tree seedlings. While previous studies have established that drought stress elevates glutamate content in the rhizosphere of Camellia oil tree, the mechanisms through which glutamate modulates rhizosphere microbial community assembly remain unresolved.MethodsTo investigate the effects of glutamate on the rhizosphere environment under drought stress, we conducted an experiment using three-year-old potted seedlings subjected to moderate drought. These seedlings were irrigated with 50 mL of glutamate solutions at varying concentrations (0, 1, 2, 5, and 10 mmol/L; labeled G0, G1, G2, G5, and G10, respectively). Through analysis of rhizosphere soil nutrients, enzyme activity, and bacterial community abundance (relative and absolute).ResultsThe study revealed the following: Concentrations of available nitrogen forms (DON, NH4+-N, NO3–-N) increased proportionally with glutamate concentration, whereas soil pH and urease activity exhibited inverse trends. Alpha and beta diversity analyses demonstrated significant divergence in bacterial community composition across treatments. Kruskal-Wallis, ANOVA, and LEfSe analyses identified 24 bacterial phyla significantly associated with treatment differences, with their abundance patterns corresponding to nitrogen cycling gene dynamics—generally peaking at G5 before declining.DiscussionThese findings collectively suggest that 5 mmol/L Glu represents a pivotal concentration influencing rhizosphere bacterial community dynamics in Camellia oil tree under drought stress.